Anonymous Cluster-Based MANETs with Threshold Signature. (25th March 2013) - Park, YoHan; Park, YoungHo; Moon, SangJae
Abstract : Security supports are a significant factor in the design of security system in ad hoc networks. It is particularly important to protect the identities of individual nodes to avoid personal privacy concerns. In this paper, we propose a security system for ID-based anonymous cluster-based MANETs to protect the privacy of nodes. Moreover, we propose a threshold signature scheme without pairing computations, which diminishes the computation load on each node. To the best of our knowledge, our proposed security system is the first in which the pseudonym is combined with cluster-based mobile ad hoc networks (MANETs) without a trusted entity. According to our protocol analysis, our proposal satisfies most properties for an anonymous security system and effectively copes with dynamic environments with greater efficiency by using secret sharing schemes. Therefore, it could be usefully applied to preserve privacy in dynamic MANETs without a trusted entity, such as military battlefields, emergency areas, mobile marketplaces, and vehicular ad hoc networks (VANETs).